2003
DOI: 10.1038/sj.bjc.6600766
|View full text |Cite
|
Sign up to set email alerts
|

Molecular classification of synovial sarcomas, leiomyosarcomas and malignant fibrous histiocytomas by gene expression profiling

Abstract: In this study, we have used genome-wide expression profiling to categorise synovial sarcomas, leiomyosarcomas and malignant fibrous histiocytomas (MFHs). Following hierarchical clustering analysis of the expression data, the best match between tumour clusters and conventional diagnosis was observed for synovial sarcomas. Eight of nine synovial sarcomas examined formed a cluster that was characterised by higher expression of a set of 48 genes. In contrast, sarcomas conventionally classified as leiomyosarcomas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 18 publications
2
62
0
1
Order By: Relevance
“…Hierarchical clustering demonstrated leiomyosarcoma and MFH shared a similar protein expression profile, some of which was not distinguishable on the basis of protein expression, and that clear cell sarcoma, synovial sarcoma, and MPNST were grouped according to their protein expression patterns. These results were generally consistent with previous reports based on histologic and transcriptome analyses [7,13,19,25,[30][31][32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hierarchical clustering demonstrated leiomyosarcoma and MFH shared a similar protein expression profile, some of which was not distinguishable on the basis of protein expression, and that clear cell sarcoma, synovial sarcoma, and MPNST were grouped according to their protein expression patterns. These results were generally consistent with previous reports based on histologic and transcriptome analyses [7,13,19,25,[30][31][32].…”
Section: Discussionsupporting
confidence: 93%
“…Fletcher et al [7] examined 100 cases of so-called MFH histologically and reclassified 20 of the cases as leiomyosarcomas. Considering these findings together with recent DNA microarray and comparative genomic hybridization analyses [25,31,32], at least a proportion of MFHs should be reclassified as a pleomorphic subtype of leiomyosarcoma. In this context, pleomorphic leiomyosarcoma and MFH shared similar expression patterns of tropomyosin isoforms.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, cytogenetic data indicate that differences in genomic aberrations may be related to tumor localization rather than to tumor morphology. 43 Despite these constraints, UPS and LMS have been shown to cluster together in earlier gene expression studies [3][4][5][6]44 and to be indistinguishable in studies that have applied proteomic profiling. 45,46 Histologic pleomorphism has been suggested to play a role with closer similarity …”
Section: Prognostic Correlationsmentioning
confidence: 99%
“…It is tempting to speculate that target genes of the SYT-SSX protein, which is thought to function as an aberrant transcriptional regulator, are associated with epithelial differentiation, because the SYT-SSX2 fusion is almost exclusively found in monophasic SS, whereas biphasic SS usually contain the SYT-SSX1 fusion (Kawai et al, 1998;Antonescu et al, 2000;Ladanyi et al, 2002). Recent microarray-based expression profiling studies of SS have identified genes that appear differently expressed between SS and other SCS or monophasic and biphasic histology (Allander et al, 2002;Nagayama et al, 2002;Nielsen et al, 2002;Lee et al, 2003;Segal et al, 2003). ELF3, for example, was identified as one of the genes differentially overexpressed in biphasic cases, compared to monophasic tumors (Allander et al, 2002).…”
Section: Discussionmentioning
confidence: 99%